Analisis Kaidah Universalitas dan Historisitas Teks Agama, dan Implementasinya dalam Ahkam Al-Usrah - Ahmad Zuhairuz Zaman (Mabahits : Jurnal Hukum Keluarga Islam, 2021)
This study discusses two rules that attract each other in an effort to understand the meaning behind the text of law both in the form of verses and hadith. The two rules are the rule of